Electronic medical records: an empirical study of South African health workers' attitudes, use and perceptions of impacts - Katsande, Tinashe (My University, 2014)
Successful implementation of electronic medical record systems (EMRs) can result in many benefits. However, the adoption and use of EMRs by health workers is often problematic. Understanding the perceptions and attitudes of health workers towards the use of these systems is therefore important. This study has contributed by examining (a) perceptions of health workers towards the characteristics of EMR systems, (b) perceptions of the impacts of EMR use on healthcare delivery and other workplace outcomes (i.e. individual work performance and job satisfaction), (c) their intentions to continue using EMRs. The DeLone and McLean Information System Success model and the Information Systems Continuance model were used to underpin the study and to hypothesize inter-relationships amongst these perceptions and attitudes. The empirical context of the study was Tygerberg Hospital in Cape Town, South Africa. A survey was carried out and 142 responses were obtained from the nurses at the hospital. Results showed that system characteristics, namely, system quality, information quality and service quality were significant predictors of user satisfaction, which in turn was found to be a significant predictor of EMR use. Satisfaction together with perceptions of individual impacts and healthcare impacts was found to lead to continuance intention. Users reported statistically significantly higher levels of job satisfaction than non-users. Healthcare impact perceptions was positively associated with job satisfaction. Based on the results of the study, it is recommended that decision makers, policy makers and EMR vendors pay close attention to the service quality and the system quality of EMRs as these are the key determinants of user satisfaction. It is also recommended that managers ensure that all healthcare workers be given access to and encouraged to use EMRs to perform their work related task as EMR users have been shown to have higher levels of job satisfaction than non-users.
Thesis (M.Com. (Information Systems))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2014.
Keywords: Electronic medical records; EMR; Perceived impacts; DeLone and McLean; Bhattacherjee; Information systems; Job satisfaction